Mehta’s Modification of Crawford’s Technique for Frontalis Sling Surgery With Silicone Rod - Anuj Mehta; Sangeeta Abrol; Prerna Garg (Delhi Journal of Ophthalmology)
Fox’s Pentagon is the most commonly used technique for passing the Silicone rod in ptosis. In certain special conditions like predominantly lateral droop, it may not give optimal results. We have devised a new technique of passing the Silicone rod, which is a modification of Crawford’s technique. This new technique is very easy to perform with very good postoperative results. The advantages include control over the curvature of lid, a good postoperative lid crease, minimal lagophthalmos, no forehead scar and no central focal notching.